2018
DOI: 10.1080/13811118.2017.1372827
|View full text |Cite
|
Sign up to set email alerts
|

When Doctors Struggle: Current Stressors and Evaluation Recommendations for Physicians Contemplating Suicide

Abstract: The objective of this study was to document current risk factors associated with physicians' suicide ideation among a group of doctors enrolled in a Physician Health Program. A retrospective cohort study was drawn from administrative data. The study compared intake information between doctors who reported recent thoughts of suicide (n = 70) and those who did not (n = 1,572) using adjusted regression analysis. Current stressors included personal, financial, health, and occupational problems; ideation was more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 23 publications
1
32
0
1
Order By: Relevance
“…The finding that 8% of the individuals with "absence of psychopathology" presented suicide risk is in line with the literature stating that not all who present suicide risk must have a psychiatric illness, but rather could also be associated with factors such as job problems or a crisis in a work situation and the inability to cope with them (Brooks, Gendel, Early, & Gundersen, 2018;Gold et al, 2013;Mingote Adan et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…The finding that 8% of the individuals with "absence of psychopathology" presented suicide risk is in line with the literature stating that not all who present suicide risk must have a psychiatric illness, but rather could also be associated with factors such as job problems or a crisis in a work situation and the inability to cope with them (Brooks, Gendel, Early, & Gundersen, 2018;Gold et al, 2013;Mingote Adan et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…In those 61 articles, 55 articles were on physicians [1,5,7,8,15,16,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,82,83,84,85], four on dental surgeons [55,…”
Section: Resultsmentioning
confidence: 99%
“…67 Moreover, women physicians are more than two times more likely to report thoughts of suicide than men physicians. 68 In medical students, one study found that symptoms of burnout seemed to be associated with future suicidal ideation, while suicidal ideation decreased upon recovery from burnout. 56 Burnout in women physicians In 2017, the percentage of women physicians in active practice was reported at 35.2%, 16 and the percentage of women among medical school matriculants passed the 50% mark for the first time.…”
Section: Physicians From Underrepresented Groups and Risk For Leavingmentioning
confidence: 99%